Binge‐Pattern Ethanol Exposure During Adolescence, but Not Adulthood, Causes Persistent Changes in GABAA Receptor‐Mediated Tonic Inhibition in Dentate Granule Cells. (15th February 2013) - Fleming, Rebekah L.; Li, Qiang; Risher, Mary‐Louise; Sexton, Hannah G.; Moore, Scott D.; Wilson, Wilkie A.; Acheson, Shawn K.; Swartzwelder, H. Scott
<x xml:space="preserve">Abstract</x> Background In recent years, it has become clear that acute ethanol (EtOH) affects various neurobiological and behavioral functions differently in adolescent animals than in adults. However, less is known about the long‐term neural consequences of chronic EtOH exposure during adolescence, and most importantly whether adolescence represents a developmental period of enhanced vulnerability to such effects. Methods We made whole‐cell recordings of GABAA receptor‐mediated tonic inhibitory currents from dentate gyrus granule cells (DGGCs) in hippocampal slices from adult rats that had been treated with chronic intermittent ethanol (CIE) or saline during adolescence, young adulthood, or adulthood. Results CIE reduced baseline tonic current amplitude in DGGCs from animals pretreated with EtOH during adolescence, but not in GCs from those pretreated with EtOH during young adulthood or adulthood. Similarly, the enhancement of tonic currents by acute EtOH exposure ex vivo was increased in GCs from animals pretreated with EtOH during adolescence, but not in those from animals pretreated during either of the other 2 developmental periods. Conclusions These findings underscore our recent report that CIE during adolescence results in enduring alterations in tonic current and its acute EtOH sensitivity and establish that adolescence is a developmental period during which the hippocampal formation is distinctively vulnerable to long‐term alteration by chronic EtOH exposure.